Performance study of flat plate heat pipe using laser holographic interferometry - Sun, Kian Hooy (2009)
The velocity profiles in the vapour region of a flat plate heat pipe were studied. Both symmetrical and asymmetrical conditions were considered. The vapour pressure distribution was solved by introducing a stream function into the incompressible Navier-Stokes equations. The results obtained were compared with the numerical and experimental data and the agreement was found to be reasonably good. Using Darcy's equation as the momentum equation, the liquid pressure distribution was also obtained. The pressure profiles for both phases were presented.